War on Carcinogens: Industry Disputes Human Relevance of Chemicals Causing Cancer in Laboratory Animals Based on Unproven Hypotheses, Using Kidney Tumors as an Example. (1st October 2013) - Melnick, Ronald L; Ward, Jerrold M; Huff, James
<x xml:space="preserve">Abstract</x> Evidence from studies in animals is essential for identifying chemicals likely to cause or contribute to many diseases in humans, including cancers. Yet, to avoid or delay the implementation of protective public health standards, the chemical industry typically denies cancer causation by agents they produce. The spurious arguments put forward to discount human relevance are often based on inadequately tested hypotheses or modes of action that fail to meet Bradford Hill criteria for causation. We term the industry attacks on the relevance of animal cancer findings as the "War on Carcinogens." Unfortunately, this tactic has been effective in preventing timely and appropriate health protective actions on many economically important yet carcinogenic chemicals, including: arsenic, asbestos, benzene, 1, 3-butadiene, formaldehyde, methylene chloride, phthalates, tobacco usage, trichloroethylene [TCE], and others. Recent examples of the "War on Carcinogens" are chemicals causing kidney cancer in animals. Industry consultants argue that kidney tumor findings in rats with exacerbated chronic progressive nephropathy (CPN) are not relevant to humans exposed to these chemicals. We dispute and dismiss this unsubstantiated claim with data and facts, and divulge unprofessional actions from a leading toxicology journal.